(untitled) (Prakriti - The International Multidisciplinary Research Journal, 2026)
Coastal land is very dynamic in nature. It can experience change due to natural and anthropogenic activities. If the area is a popular tourist destination, then it emerges more rapidly than other parts. Land use and Landcover analysis depicts all in them. The present paper is about those changes in the selected tract of coastal land along east coast of India. It is based on secondary data like satellite images majorly. It depicts periodic change in land use and landcover from Talsari to Udaypur (1932 -2022). The LULC of different time frame shows the nature of change in the area.